Pengaruh Kompetensi dan Kredibilitas Chatbot AI Terhadap Kepercayaan Penggunaan Chatbot AI Pada Pengguna Lazada Di Kota Medan: Pengaruh Kompetensi dan Kredibilitas Chatbot AI Terhadap Kepercayaan Penggunaan Chatbot AI Pada Pengguna Lazada Di Kota Medan - Mutyara, M Reza Aldiansyah; Hasman, Haryaji Catur Putera; Alfifto, Alfifto; Darmansyah, Mutya Rahmi (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This research aims: (1) To determine the influence of AI Chatbot on purchase intentions of Lazada users in the city of Medan; (2) To determine the effect of trust on purchase intentions among Lazada users in the city of Medan. (3) To determine the effect of AI Chatbot on purchase intention with trust as a mediating variable among Lazada users in the city of Medan. This research method uses quantitative methods. The research sample was 5 sub-districts represented by 170 respondents. Research results: (1) Chatbot AI has a positive and significant effect on Trust among Lazada users in the city of Medan; (2) Trust has a positive and significant effect on Purchase Intention of Lazada users in the city of Medan. (3) AI chatbot has a positive and significant effect on Purchase Intention of Lazada users in the city of Medan.